2005
DOI: 10.1007/s11214-005-3387-3
|View full text |Cite
|
Sign up to set email alerts
|

Deep Impact: A Large-Scale Active Experiment on a Cometary Nucleus

Abstract: The Deep Impact mission will provide the first data on the interior of a cometary nucleus and a comparison of those data with data on the surface. Two spacecraft, an impactor and a flyby spacecraft, will arrive at comet 9P/Tempel 1 on 4 July 2005 to create and observe the formation and final properties of a large crater that is predicted to be approximately 30-m deep with the dimensions of a football stadium. The flyby and impactor instruments will yield images and near infrared spectra (1-5 µm) of the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…The Deep Impact mission to the Comet 9P/Tempel 1, generally have confirmed many presumptions related to the physics of comets (A'Hearn et al 2005). That is why calculations which were carried out and reviewed in this paper and which are based on the hitherto existing model of a cometary impact with a meteoroid (Gronkowski 2004a), are quite proper to describe the results of such events at least as far as the changes in the cometary brightness are concerned.…”
Section: Remarkssupporting
confidence: 52%
“…The Deep Impact mission to the Comet 9P/Tempel 1, generally have confirmed many presumptions related to the physics of comets (A'Hearn et al 2005). That is why calculations which were carried out and reviewed in this paper and which are based on the hitherto existing model of a cometary impact with a meteoroid (Gronkowski 2004a), are quite proper to describe the results of such events at least as far as the changes in the cometary brightness are concerned.…”
Section: Remarkssupporting
confidence: 52%
“…The Deep Impact mission (A'Hearn et al 2005a) successfully placed a 364 kg impactor onto the surface of comet 9P/Tempel 1 at a relative velocity of 10.3 km s −1 on 2005 July 4 at 05:52:03 UT (as seen from Earth). The event was observed by cameras aboard the mother spacecraft (A'Hearn et al 2005b) and by a large number of Earth-and space-based telescopes as part of an extensive campaign to study the comet prior to, during, and in the course of several days following the impact (Meech et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The SST observations confirmed that Tempel 1's thermal inertia was very low, less than that of the Moon, giving confidence that the standard thermal model for slow rotators is valid. And indeed, the conversion of radiometry to nucleus size was confirmed by the Deep Impact flyby, which encountered a nucleus of effective radius 3.0 ± 0.1 km (A'Hearn, Belton, Delamere, et al 2005). …”
Section: Thermal Propertiesmentioning
confidence: 87%
“…In July 2005, the Discovery-class spacecraft Deep Impact delivered a 10-km/s impactor onto the surface of this comet (A'Hearn, Belton, Delamere, et al 2005). Spitzer's IRS observed the exact moment of impact, taking 5.2-8.7 µm spectra with high temporal frequency to watch the rapidly changing post-impact environment (van Cleve, Lisse, Grillmair, et al 2005).…”
Section: Dustmentioning
confidence: 99%